If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12a + -5b = 27 Solving -12a + -5b = 27 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '5b' to each side of the equation. -12a + -5b + 5b = 27 + 5b Combine like terms: -5b + 5b = 0 -12a + 0 = 27 + 5b -12a = 27 + 5b Divide each side by '-12'. a = -2.25 + -0.4166666667b Simplifying a = -2.25 + -0.4166666667b
| 3z=z+26 | | r/320 | | 4n-2n+4=1+17 | | 4v-3+8=13 | | -1/2w-7/5=4/3 | | 3+3(2-6)squared= | | -8a-2a=-10 | | b+4=2b-3 | | -x-8=x+2 | | -4(5x-4)+3(4x+2)= | | 6n-3=3n-15 | | 2(2x+2)-3(x-4)= | | A/2=36 | | 84=78+n | | -x+7x=-12 | | -x^2+5=(4x-1)(4x-1) | | 4a+7a=7a+16 | | v/-4=13 | | -0.25+0.6= | | -0.25-0.6= | | (13m-11)=2m+5 | | -6(b-6)+4=88 | | 4.5s-s= | | 0.25-0.6= | | x*3+75=x*9-9 | | 18x11/(18x11)= | | 13m-11=2m+5 | | 2v-1=11 | | 63=2(6x-1)+5 | | 16a-5a= | | d+d+3d= | | -66=6(1+4m) |